2014
DOI: 10.1007/s10529-014-1514-5
|View full text |Cite
|
Sign up to set email alerts
|

Quorum sensing activity and control of yeast-mycelium dimorphism in Ophiostoma floccosum

Abstract: José, "Quorum sensing activity and control of yeastmycelium dimorphism in Ophiostoma floccosum" (2014). Faculty Publications in the Biological Sciences. 560.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Interestingly, other authors did not find any effect of farnesol on O. ulmi (4,26,33). In this sense, the O. piceae strain studied in this work is a saprophyte and affiliates phylogenetically with the nonpathogenic species of the Ophiostoma clade, such as O. quercus, far from the pathogens O. ulmi and O. novo-ulmi (see Fig.…”
Section: Resultsmentioning
confidence: 51%
“…Interestingly, other authors did not find any effect of farnesol on O. ulmi (4,26,33). In this sense, the O. piceae strain studied in this work is a saprophyte and affiliates phylogenetically with the nonpathogenic species of the Ophiostoma clade, such as O. quercus, far from the pathogens O. ulmi and O. novo-ulmi (see Fig.…”
Section: Resultsmentioning
confidence: 51%
“…Similarly, Hammami et al (2010, 2011) demonstrated pseudo-hyphal growth of P. flocculosa under stress conditions as compared to yeast-like growth under control conditions (Hammami et al, 2010, 2011). In many other dimorphic fungi, the morphological choice of yeast or mycelium is associated with quorum sensing, inoculum size, stress conditions and secreted molecules (Hornby et al, 2001, 2004; Hogan, 2006; Nickerson et al, 2006; Berrocal et al, 2014). Since we did not observed coiling or the formation of long hyphae when P. aphidis interacted with B. cinerea , we assume that the interaction with powdery mildew triggers this yeast–mycelia transition, probably involving molecule secretion or other cues that activate gene expression and need to be further characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Dimorphism is a peculiar characteristic of several yeast species and filamentous fungi, such as Candida albicans, Saccharomyces cerevisiae, Yarrowia lypolitica, Pichia fermentans, Schizosaccharomyces japonicus, Ustilago maydis, Ophiostoma floccosum, Ceratocystis ulmi, Mycosphaerella graminicola, which can switch between unicellular yeast and multicellular filamentous growth forms in response to changing environmental cues [1][2][3][4][5][6][7][8]. Usually, in the yeast stage, mitotic divisions either by budding or fission to produce two independent cells, while in the filamentous stage, cells become elongated yet fail to abscise following cytokinesis, and remain attached to form chains of elongated pseudohyphal cells; the true hyphae are produced with long continuous tubes and septae separating each of the nuclei in these tubes [2].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in order to facilitate better control of morphology switch CONTACT Ri Ming Yan rimingyan@163.com; yanriming@jxnu.edu.cn; Du Zhu zhudu12@163.com *Both authors contributed equally to this work and further understanding of the dimorphic transitions mechanisms, a great number of investigations into the nutritional and environmental stimuli which can induce dimorphic transitions have been conducted. Previous investigations have documented that dimorphic transition is normally induced by a variety of environmental and nutritional factors including temperature [9], quorum sensing molecules [5], inoculum size [16], the accessibility of nitrogen source [14] and carbon [17], the concentration of serum [7], amino acid [18], pH [19] and so on. Despite many different environmental factors that can induce dimorphism transition, the signalling pathways involved in connecting external stimuli and cell morphological transformation are highly conserved even among distantly related fungi [14,20].…”
Section: Introductionmentioning
confidence: 99%